FREQUENCY OF HEALTH RELATED MYTHS AMONG FEMALES ADMITTED IN A TERTIARY CARE HOSPITAL: Health Related Myths - Waseem, Aneeqa; Waseem, Waseem; Lehrasab, Iram; Nadeem, Bushra (Pakistan Armed Forces Medical Journal, 2018)
Objective: To study frequency of myths about disease, to assess awareness among people andto propose methodology to bring changes in the attitude of community. Study Design: Descriptive cross-sectional survey. Place and Duration of Study: Family Wing of Combined Military Hospital Multan, from Oct 2016 to Apr 2017. Patients and Methods: A sample of 200 female patients was taken and a questionnaire containing close-ended questions in both Urdu and English languages was used to obtain knowledge of female patients about various health related myths. Results: Almost 24% of patientsthought that myth practitioners are trained and qualified. This belief has no boundaries even where education is concerned. The percentage of individuals believing in myths was 40.7% among the „Matric to Bachelors‟ category whereas among the respondents having „Master and Post-graduation‟ it was 16.66%, rest of the believers i.e. 42.64% were under matric. Conclusion: Femalesin Pakistan still believe in preconceived ideas as a cause of their illness seeking treatment from mythical practices. According to our findings, alternative options of medicine are still a popular option for patients rather than opting for allopathic medicine. Cognition for allopathic treatment options is very poor and cultural influence is deeply engrained while religious knowledge is lacking, resulting in less acceptability of modern technologies.